Finite Element Analysis of Creep Crack Initiation in Functionally Graded Materials with Crack Parallel to the Gradient - Huan Sheng Lai; Chunmei Bai; Kang Lin Liu (International Journal of Architectural Engineering Technology, 2019)
With the advances in material synthesis technologies, functionally graded materials (FGMs) are developed to use in high temperature structurals due to the excellent high temperature mechanical properties. To facilitate wide use of FGMs in high temperature structures, finite element method (FEM) was used in this paper to investigate effects of creep resistant properties gradients on creep crack initiation (CCI) in FGMs, with crack parallel to the gradient. Results indicated that when creep resistant properties increased in the crack growth direction, CCI was retarded by creep properties gradients. However, CCI was accelerated by creep properties gradients when creep resistant properties decreased in the crack growth direction. CCI position occurred in the two symmetric slanted planes of the initial crack, regardless of the gradient variation of creep resistant properties.